O‘QUV JARAYONLARIDA SUN’IY INTELLEKT VOSITALARIDAN FOYDALANISH - Hursandov, H.F.; Ahtamqulov, M.A.; Taniyeva, F. (SCIENCE and SOCIETY, 2025)
In this article are studied and analyzed several effective possibilities of using artificial intelligence tools in educational processes. The concept of artificial intelligence and various modern methods of its use in educational processes are compared and considered in detail. Educational features of artificial intelligence tools are also analyzed. In addition, the authors of the article suggest various methods of increasing the effectiveness of the educational process based on artificial intelligence tools. The positive effects of artificial intelligence tools are discussed on the field of education.